Leadership for Inclusive Education Values, Vision and Voices - Ruairc, G. Mac.; Ottesen, E.; Precey, R.; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2013)
Inclusion is increasingly becoming one of the policy drivers shaping educational discourse and practice. What constitutes the term (3z(Binclusion(3y (Bitself and how ideas derived from the different perspectives on inclusion impact school leadership practice point to a highly contested field of enquiry. Originally embedded in discourse relating to special education, ideas relating to inclusion are attracting much broader appeal within system reforms in many jurisdictions. This book seeks to keep the consideration of inclusion firmly in its broader context and to decouple it from the discourse relating to students with special educational/additional needs. This allows the authors to position their contributions more explicitly within discourses that draw on difference and diversity as unavoidable features of schools. Within this collection we address the current political dogmas in many countries that take a purely rational, managerial approach to leadership, arguing that this is not contributing to inclusion in schools. In doing this, the book seeks to shape current discourses on leadership by exploring perspectives which are likely to enhance our understanding of inclusion. Tolerance, respect, listening, clarifying language, being comfortable with differences and ambiguity and articulating and challenging the rationale behind (3z(Bthe way we do things around here(3y (Bare key aspects of inclusive leadership, and also fundamental imperatives for writing this book. It will be useful to those in education who are engaged in further academic study in education or in reflective practice and to anyone taking advanced programmes in educational leadership and management. The international perspectives on the issue of inclusion informing this book ensure that this book will be essential for those engaged in a comparative analysis of leadership practice in different contexts or those concerned with the complexity of ensuring inclusive models of education.s
Keywords: Education; Education; Education (general).